Who watches the watchment? Evaluating judicial performance in the American states - Paynter, Sharon; Kearney, Richard C. (2010)
Scholars and human resource practitioners agree that effective performance appraisal systems have clear objectives, reliable and valid appraisal methodology, separation of personal judgments from job-based performance assessments, acceptance by employees, and leadership commitment. Using data from state reports, surveys, case histories, personal interviews, and judicial performance appraisal studies, this article juxtaposes judicial performance evaluation (JPE) and the criteria for effective appraisal systems to address the question of whether judicial independence can be preserved when judges' performance is systematically evaluated by multiple raters. The authors conclude that JPE is an effective performance appraisal tool that can satisfy the need for accountability to the public while protecting judicial independence. - Reproduced.
Keywords: Performance appraisal - united States; Courts - United States; Judiciary - United States; Judiciary